Bone-Derived Extracellular Vesicles: Novel Players of Interorgan Crosstalk - Li, Yi; Yin, Pengbin; Guo, Zhongkui; Lv, Houchen; Deng, Yuan; Chen, Ming; Gu, Ya; Tang, Peifu; Zhang, Licheng (Frontiers in Endocrinology, 2019)
An increasing number of studies have shown that bone plays an active role in regulating glucose metabolism, affects renal and cardiovascular diseases and even influences the development of offspring. These novel findings have indicated that bone plays a much more important role in the human body than only providing physical support. However, further investigations of the mechanisms underlying the effects of bone are needed. Recently, extracellular vesicles (EVs) have received increased attention because they can transfer functional proteins, mRNAs, and miRNAs between cells/organs. After reviewing the existing evidence, we hypothesized that bone may be involved in interorgan communication via EVs. Further research exploring bone-derived EVs may facilitate the understanding of bone as a multifunctional organ.